Maternal and neonatal outcomes in obstetric antiphospholipid syndrome: a retrospective case-control study - Rao, Lin; Lu, Jia; Li, Hong; Xu, Liang; Yang, Dongjian; Han, Wendong; Chen, Li (Frontiers in Medicine, 2025)
ObjectiveThe combination of low-dose aspirin (LDA) and low-molecular-weight heparin (LMWH) is the standard of care for obstetric antiphospholipid syndrome (OAPS), significantly improving live birth rates. However, whether this regimen fully normalizes the pregnancy course and mitigates risks for both the mother and the neonate remains unclear. This study aimed to systematically evaluate whether significant maternal and neonatal morbidity persists in OAPS patients despite successful treatment and live birth.MethodsThis retrospective cohort study included 256 OAPS patients, including 166 criteria OAPS patients (C-OAPS—patients who fulfilled both the clinical and laboratory criteria of the Sydney criteria) and 90 non-criteria OAPS patients (NC-OAPS—patients who fulfilled only the clinical or only the laboratory criteria of the Sydney criteria) who achieved live birth, along with 768 matched healthy controls. We compared basic characteristics, laboratory parameters, and perinatal outcomes between the groups.ResultsCompared to healthy controls (n = 768), treated OAPS patients (n = 256) exhibited a persistent hypercoagulable state (elevated D-dimer and fibrin degradation product (FDP), p < 0.01) and a higher incidence of anemia (p < 0.001). Their neonates had significantly lower birth weight (p = 0.006) and elevated risks of neonatal infection (adjusted OR = 3.12, p = 0.004) and hyperbilirubinemia (adjusted OR = 2.06, p = 0.024), with the infection risk remaining significant in full-term infants. A subgroup analysis revealed no significant differences in obstetric history, maternal complications, comorbidities, and outcomes between the C-OAPS and NC-OAPS groups.ConclusionDespite standard treatment, OAPS patients who deliver successfully remain at an increased risk for persistent maternal hypercoagulability and adverse neonatal outcomes. These findings underscore the need for a paradigm shift in management—from merely ensuring live birth to safeguarding neonatal health through proactive, multidisciplinary perinatal care.